2019
DOI: 10.29252/jhc.21.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress of Nurses in Emergency Department of Ardabil Hospitals in 1395

Abstract: Background & objectives:Nurses, as the main members of the care and treatment teams, are at the forefront of health care provision and their performance largely determine the quality of health care. Moral distress can have many physical and psychological consequences in nurses and negatively affect their professional responsibilities. The aim of this study was to determine the extent of moral distress in nurses of emergency department of Ardabil hospitals in 2016. Methods: This descriptive-analytical study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the study of de Lima Dalmolin et al, a weak correlation was noticed between moral distress and job burnout (20). Moreover Anami et al reported a statistically significant direct correlation of three factors, i.e., employment status, shift work and the type of hospital, to moral distress (21).…”
Section: Organizations Will Pay For the Oncoming Consequencesmentioning
confidence: 99%
“…In the study of de Lima Dalmolin et al, a weak correlation was noticed between moral distress and job burnout (20). Moreover Anami et al reported a statistically significant direct correlation of three factors, i.e., employment status, shift work and the type of hospital, to moral distress (21).…”
Section: Organizations Will Pay For the Oncoming Consequencesmentioning
confidence: 99%
“…Another study revealed environmental empowerment as a factor with negative relationship with MD (20). Moreover, some studies reported employment status, time limitation due to excessive working hours, and inability to challenge the decisions of other healthcare professionals as the contributing factors of MD (5,10,16,13,21,22). Given the significant relationship of MD with age and work experience, nurses with lower age and work experience should work with older and more experienced colleagues in order to experience lower MD.…”
Section: Personal Factorsmentioning
confidence: 99%
“…Moreover, a study showed that 75% of pediatric nurses and 58.8% of critical care nurses experienced low MD and 25% of pediatric nurses and 41.2% of critical care nurses experienced moderate MD. Moreover, the mean score of MD among critical care nurses was significantly more than pediatric nurses (58.02 vs. 37.48) (10). MD may be associated with many different problems for nurses such as burnout, low job satisfaction, low quality of care, and intention to leave the profession (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency department personnel, experience working in unpredictable and critical conditions that inevitably influences their clinical decisions (8). In Dadkhah study (2016) in the ward, it was revealed that the extent of nurses' moral distress in emergency department was reported as being average (9).…”
Section: Introductionmentioning
confidence: 99%